Multidrug-Resistant Organism Carriage in Wisconsin Children. (October 2020) - Kates, Ashley; Putman-Buehler, Nathan; Watson, Lauren; LeCaire, Tamara; Malecki, Kristen; Peppard, Paul; Sethi, Ajay; Wald, Ellen; Mares, Julie; Shirley, Daniel; Suen, Garret; Safdar, Nasia
Abstract : Background: Children attending daycare are at increased risk of carrying multidrug-resistant organisms (MDROs) compared to children not attending daycare. Carriage of MDROs greatly increases the risk of infection, not only in the child but also for others living in the household. Understanding the epidemiology of MDRO carriage in children is essential to devising effective containment strategies. Here, we present the findings from a cross-sectional study assessing MDRO carriage in daycare-attending and nonattending children in Wisconsin. Methods: We applied the following enrollment criteria: Children aged between 6 months and <6 years and not enrolled in kindergarten; children who did not have an MDRO infection in the previous 6 months and did not receive any antimicrobials in the previous month; and children who did not have a gluten allergy, asthma, eczema, allergic rhinitis, cystic fibrosis, or an immunodeficiency. Children were enrolled by a parent or guardian who filled out a questionnaire on MDRO risk factor history and diet. Samples were collected from the nares, axilla or groin (pooled swab), and stool. Nasal samples were cultured for H. influenzae, S. pneumoniae, M. catarrhalis, and methicillin-resistant S. aureus (MRSA). Skin samples were cultured for MRSA, and stool samples were cultured for MRSA, C. difficile, vancomycin-resistant enterococci (VRE), and extended-spectrum β-lactamase–producing Gram-negative bacilli (ie, ESBL GNR). Results: In total, 44 children were enrolled in this study. The average age was 2.6 years and 50% were girls. Furthermore, 30 (68.2%) were identified by their parents as white, 9 (20.5%) as black, and 5 (11.3%) as other or multiracial. Incidentally, 23 children (52.3%) were enrolled in daycare. Overall, 18 children were positive for at least 1 organism, 9 of which had daycare exposure, and 5 children (1 in daycare) were positive for >1 organism (11.4%). From stool samples, 6 children (13.6%, 2 in daycare) were C. difficile carriers, 3 were VRE carriers (6.8%, 1 in daycare), 8 carried an ESBL GNR (18.2%, 4 in daycare), and 3 carried MRSA (6.8%, 1 in daycare). One child was positive for H. influenzae (2.3%, not in daycare) and 2 were positive for S. pneumoniae (4.6%, 1 in daycare) from nares swabs. One child was positive for MRSA (2.3%, not in daycare) from a skin swab. We detected no significant differences between children with and without daycare exposure for any organism. Conclusions: Children in this population had higher than expected rates of ESBL GNRs and MRSA for a community population. Daycare exposure was not correlated with increased carriage in this small pilot study, though larger longitudinal studies are needed. Funding: None Disclosures: None